Teller test with functional vision evaluation in children with low vision - Zimmermann,Anita (2015)
ABSTRACT Objective: To know the effectiveness of Teller card test along with the functional vision evaluation in low vision preschool children presenting normal or delayed development. Methods: Transversal study comprising patients from the children visual stimulation Ambulatory Service of the Faculty of Medical Sciences, University of Campinas Teaching Hospital, Campinas (SP)(FCM/HC/ Unicamp). The best corrected visual acuity was obtained using Teller cards and functional vision evaluation, independent from the child development. Results: From a total of 143 evaluated children, 65% did not respond to the Teller card test, only to, the functional vision evaluation. Among 143 children, 99 (70%) presented development delay and 44 (30%), normal development. Conclusion: The Teller card test was not enough to evaluate the children visual acuity with development delays, since more than half of them were not responsive to it, making it necessary that they were submitted to a complementary functional visual evaluation.